2015
DOI: 10.1088/0953-8984/27/23/235105
|View full text |Cite
|
Sign up to set email alerts
|

A general theory of kinetics and thermodynamics of steady-state copolymerization

Abstract: Kinetics of steady-state copolymerization has been investigated since 1940s. Irreversible terminal and penultimate models were successfully applied to a number of comonomer systems, but failed for systems where depropagation is significant. Although a general mathematical treatment of the terminal model with depropagation was established in 1980s, penultimate model and higher-order terminal models with depropagation have not been systematically studied, since depropagation leads to hierarchically-coupled and u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Following the same logic of Ref. 29, we use P s Xn···X 1 to denote the occurrence probability of the terminal sequence X n · · · X 1 in the synthetic (polymerase) site, P e Xn···X 1 to denote the occurrence probability of X n · · · X 1 in the exonuclease site, X i = A, B. N Xn···X 2 X 1 is defined as the total number of sequence X n · · · X 2 X 1 appearing in the primer chain.…”
Section: A First-order Proofreading Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the same logic of Ref. 29, we use P s Xn···X 1 to denote the occurrence probability of the terminal sequence X n · · · X 1 in the synthetic (polymerase) site, P e Xn···X 1 to denote the occurrence probability of X n · · · X 1 in the exonuclease site, X i = A, B. N Xn···X 2 X 1 is defined as the total number of sequence X n · · · X 2 X 1 appearing in the primer chain.…”
Section: A First-order Proofreading Modelmentioning
confidence: 99%
“…This method has already been used for higher-order copolymerization by us (see the supplementary of Ref. 29) and can be readily extended to the exonuclease proofreading schemes.…”
Section: The Fidelity Problem Of Dna Replication By Dnapmentioning
confidence: 99%
See 1 more Smart Citation
“…As suggested by previous work [21,22] devoted to the k = 0 and k = 1 cases, k th -order Markov chains are generated if the kinetics depends on k lastly incorporated monomeric units [23]. In the present paper, the analytical method previously developed in Ref.…”
mentioning
confidence: 93%
“…These considerations have been addressed in recent kinetic formalisms of growth velocity and fidelity during the real, non-equilibrium process, these models including nearest neighbor and higher-order effects 3538 . In addition, within the context of information theory and thermodynamics of DNA replication, it has been recently shown that to keep the fidelity within a given tolerance, average consumed energy E must increase with the reliability of the incorporated nucleotide according the next relation 33 (see Methods):where p error is the sequence-independent probability of error per incorporated nucleotide (or error rate) in the absence of exonucleolytic proofreading and β  = 1/ kT .…”
Section: Discussionmentioning
confidence: 99%